Quality assessment of surface water using the Nile Chemical Pollution Index (NCPI) and microbiological pollution of the Rosetta Branch (Nile River, Egypt) - Othman, Amal A; Al-Afify, Afify DG; Abdel-Satar, Amaal M; Ramadan, Mohamed F (African journal of aquatic science, 2021)
The Rosetta Branch (Nile River, Egypt) is one of the main sources of freshwater for drinking, agricultural, and industrial activities in the Nile Delta. However, this water supply is compromised because it receives heavy loads of domestic, agricultural and industrial waste from several sources. Water samples were collected seasonally from ten sites along the Rosetta Branch during 2014-2015. The current study aimed to assess the water quality of Rosetta Branch using the Nile Chemical Pollution Index (NCPI), and a microbiological analysis, where the physical and chemical parameters of water branch were measured. Complete depletion of dissolved oxygen was recorded at the discharge points of El-Rahawy and Sobal drains, whereas COD, BOD and nutrient salts, recorded highest levels compared with the reference site of Nile River. The abundance of the major ions was in the following order: HCO 3 − > Cl − > Na + > SO 4 2− > Ca 2+ > Mg 2+ > K + . NCPI values ranged from 15 to 45 with an average of 31, where, a sudden increase was recorded at sites affected by human activity (Sites 3 and 6) to be grossly polluted, and then the water quality improved slightly farther downstream. Microbial analyses indicated that the total bacterial counts and the total diazotrophs were present in high population densities (up to 105 CFU ml −1 ). Significant differences in counts were recorded among seasons, whereas no spatial changes were recorded. The total and faecal coliforms populations exceeded the permissible limits cited by World Health Organization (WHO) for drinking water. An intensive water-quality monitoring program is recommended for the Rosetta Branch, and the treatment of wastewater prior to discharge to mitigate health problems outbreaks or any aquatic ecosystem disorders.